Saberes Ancestrales e Identidad Cultural de la parroquia Cebadas, cantón Guamote, provincia Chimborazo. - Cuji Quinlle, Rosa Angélica (2023)
The development of this research has as a primary problem affectation to the cultural identity of the Cebadas parish. Therefore, two study variables are identified: independent variable (ancestral knowledge) and dependent variable (cultural identity), so that the objective is to analyze the relationship of ancestral knowledge with the cultural identity of the Cebadas parish, Guamote canton, Chimborazo province. It is a field, bibliographical, descriptive investigation with a non-experimental design, focused on qualitative and qualitative quantitative analysis, taking into account as a research instrument (survey) the PEA (Economically Active Population) study population of this jurisdiction, made up of people over 18 years of age; In the same way, experts who make up the 2023-2027 administrative table of the GADP Cebadas and people involved with ancestral medicine. The information was processed through the statistical program IBM SPSS version 27. To determine the reliability of the research instruments, Cronbach's Alpha and Spearman's Rho methods were used to compare the hypotheses. Concluding that ancestral knowledge is not related to the cultural identity of the Cebadas parish, Guamote canton, Chimborazo province. The contribution of the people above served to verify the problem, summarized in limited knowledge of ancestral knowledge, acculturation processes, use of typical clothing, and education system that promotes the English language and not Kichwa; Therefore, it is proposed to disseminate the cultural system in a tourist interpretation center; as suggested by the sample when considering an artistic interpretation center of ancestral knowledge to convey cultural identity with 74.29%, which led to designing the proposal: "Raymi as a connecting element of ancestral knowledge to build cultural identity"; which helps to recover cultural identity, because it is a significant process for people who feel that they have lost part of their connection with their culture.